Women's experiences of long-term effects of cervical cancer and its treatment - Ntinga, Sophai Namukonda (My University, 2014)
Cervical cancer has a major impact on women’s lives especially in developing countries where it is the leading cause of death due to late presentation. Cervical cancer usually remains asymptomatic in the pre invasive and early stages until the disease is locally advanced. The treatment for cervical cancer is guided by the age and general health of the patient as well as the extent of the cancer and presence or nature of any complicating abnormalities. Radiotherapy is the major treatment modality for cervical cancer and approximately 60% of patients with cervical cancer receive radiotherapy at some point during the treatment of the disease. Cervical cancer and its treatment can result in physical, psychological and sex-related effects. Research problem, question and purpose: Little is known concerning cervical cancer treatment related effects South African women experience 12 months after completing treatment as no literature exploring this subject could be found. The research question is therefore: What long term effects do women treated for cervical cancer at an academic hospital in Johannesburg experience 12 months after completion of treatment? The purpose of the study is to explore the effects women experience after 12 months of treatment for cervical cancer with radiotherapy. Design: A qualitative method and descriptive phenomenological design was used for this study. The setting was the Department of Radiation Oncology at an academic hospital in Johannesburg. The population comprised all women diagnosed with cervical cancer who completed radiotherapy treatment 12 months prior the study. Purposive sampling was used and the sample totalled 16 (n=16). Data were collected using open-ended, unstructured interviews. Findings: The responses elicited from the interviews, women experience problems related to Physical, Social-economic. Psycho-spiritual and sexual problems of being treated for cervical cancer. Conclusion: Women experience physical problems which has an impact on their social-economical, psycho-spiritual and sexual lives as a result of long-term effects of cervical cancer and its treatment
Keywords: Cervix Neoplasms